Risk factors leading to pulmonary exacerbation in patients with cystic fibrosis: A systematic review - Danish Abdul Aziz; Syeda Khadija Fatima; Hasan Nawaz Tahir (Journal of the Pakistan Medical Association, 2021)
Objective: To ascertain major risk factors associated with pulmonary exacerbation and pulmonary function decline in cystic fibrosis. Method: The systematic review was conducted at Aga Khan University, Karachi, in September 2018, and comprised electronic search of PubMed, Ovid, Science Direct and Cumulative Index of Nursing and Allied Health Literature databases of studies conducted from January 1990 to September 2018 which were categorised into 3 sets; 1990-98, 1999-2007 and 2008-18. Studies included for review focussed on articles with pulmonary exacerbation as the health outcome indicator, and had diagnosis of cystic fibrosis as the inclusion criteria, while risk factors were the exposure terms used in the search process. References in bibliographies of the included studies were also systematically searched for relevant documents. Results: Of the 60 studies obtained, 31(51.7%) were selected; 2(6.45%) from 1990-98, 7(22.58%) from 1999-2007 and 22(70.96%) from 2008-18. Overall, 17(54.83%) were cohort studies, 7(22.5%) were cross-sectional studies, 3(9.6%) were case-control studies, 3(9.6%) were randomised controlled trials and 1(3.2%) was systematic review and meta-analysis. In terms of major risk factors, genetic mutations were cited by 4(12.9%) studies, infections and inflammatory biomarkers by 15(48.4%), nutritional deficiencies by 9(29%) and geographical and socioeconomic status by 3(9.6%) studies. Conclusion: Early identification and recognition of risk factors associated with pulmonary exacerbation can have an explicit impact on its management, leading to decreased morbidity and mortality burden in cystic fibrosis cases. Key Words: Pulmonary exacerbation, Cystic fibrosis, Risk factors, Systematic review. Continuous...